Family as a primary coronary unit of hyperten-sive or diabetic type II people (Revista de Investigaciones Universidad del Quindío, 2017)
Chronic patients have a higher risk of suffering cardiovascular events that fatally compromise their physical integrity, placing their lives at risk. Most of these cases occur at home. Objective. This work sought to determine the response capacity of relatives of individuals with high blood pressure or diabetes mellitus type 2 on the event of cardiovascular episodes that potentially compromise the lives of their family members. Methodology. This was a quantitative, descriptive, cross-sectional study using probabilistic, simple random sampling. The population selected were relatives of individuals attending the program and control of cardiovascular risk. Results. Most of the participants were women (67.5%), students (48.2%), kinship in the first degree of consanguinity (offspring 48.7%), in an age range from 21 to 30 years (34.3%), and professional educational level (48%); 55% of those interviewed reported not knowing the signals associated to these events; only 40.2% of them stated feeling able to identify the event; however, none of them identifies the “non-response to the call” as an associated condition; only 0.5% recognized the correct sequence to act as first respondents (activation of the emergency system – cardiac compressions – early defibrillation). Of the participants, 85.5% stated not knowing an automatic external defibrillator. Conclusion. The participants are not in the capacity to engage in CPR maneuvers in case their relatives require it, given the existence of large voids in knowledge of the activities they have to carry out. Additionally, they state they do not feel competent to act consequently with the situation.
Keywords: Family; Cardiopulmonary Resuscitation; Nursing Care; Cardiovascular Disease; Hypertension; Diabetes Mellitus Type 2; Stroke